Metal-Free Aerobic Oxidative Cyanation of Tertiary Amines: Azobis(isobutyronitrile) (AIBN) as a Sole Cyanide Source - Liu, Peng-Yu; Zhang, Chao; Zhao, Shi-Chen; Yu, Fang; Li, Fei; He, Yu-Peng (Journal of organic chemistry, 2017)
An aerobic oxidative cyanation for the synthesis of α-aminonitriles was reported. The formation of C(sp3)-CN bonds was achieved under a metal-free condition by utilizing azobis(isobutyronitrile) as a sole organic cyanide source with the combination of pivalic acid and sodium acetate as additives.